Pupuk Terhadap Kandungan Proksimat dan Mineral pada Suruhan Peperomia pellucida - Yusrin Anton Puluhulawa; Novri Youla Kandowangko; Margaretha Solang (Universitas Sebelas Maret, 2021)
Suruhan plant is one of the plants that has properties for treatment in various diseases such as diabetes mellitus, headache, fever, and rheumatism. The plant contains antioxidants, antimicrobials and anticancers. Proximate content analysis is important to be used as data on the content of a foodstuff. One way to increase the content to be more useful is by cultivating using organic fertilizer. The purpose of this research is to find out the influence of organic fertilizers on the content of proximate, minerals on the plants. The method used was descriptive quantitative. This research was conducted in Bua Village, Batudaa District, Gorontalo Regency. Sample preparation of surname plants was carried out at the Biology Laboratory of the State University of Gorontalo for proximate and mineral analysis carried out at the Analysis Laboratory of the Bogor Pacapanen Center. The research was carried out in August-September 2020. Based on the results showed that on the content of proximate and minerals in the commission plants given organic fertilizer obtained water content of 26.60%, ash content of 16.80%, fat content of 2.58%, protein content of 13.86%, carbohydrates 40.16%, iron (Fe) 18.74 ppm, calcium (Ca) 255.92 ppm.